Botrytis Blossom Blight of Southern Highbush Blueberry - Philip F. Harmon (EDIS)
Information contained in this publication is intended to help blueberry growers in Florida identify and manage Botrytis blossom blight. For more information, search the EDIS website (http://edis.ifas.ufl.edu) or contact your local UF/IFAS Extension agent (http://ifas.ufl.edu/extension-offices-rec-maps.shtml). This document is PP198, one of a series of the Plant Pathology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date April 2004.